Iceland : 2021 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2021)
The Icelandic economy has been severely affected by the pandemic. Sharp tourism contraction and containment measures caused real GDP to plummet by 6.6 percent in 2020. A modest recovery will take hold in 2021. Recovery prospects in the tourism sector depend on control of the epidemic and progress in global and domestic vaccine distribution, spelling a challenging outlook with possibly deep medium-term scarring. Fiscal policy should continue to support the economy for now. Policy buffers accumulated over the last decade provided space for a large fiscal support and accommodated substantial automatic stabilizers. Additional stimulus is planned in 2021 to address still large slack in the economy, mitigate scarring, and provide confidence in the event of downside risks. Medium-term policies should ensure that public debt is firmly on a downward path, while limiting the drag on growth.